Laparoscopic cholecystectomy in acute biliary pancreatitis - Girgin, Mustafa; Turkoglu, Ahmet; Ayten, Refik; Cetinkaya, Ziya; Mulla, Mustafa; Binnetoglu, Kenan (Turkish Surgical Assoc, 2011)
Purpose: Gallstones represent one of the main causes of acute pancreatitis. The aim of this study was to evaluate laparoscopic cholecystectomy results due to acute pancteatitis and compare the surgical results with patients who are operated on symptomatic cholecystolithiasis. Patients and Methods: Eighty-six patients have underwent cholecystectomy because of acute biliary pancreatitis (Group 1), 93 patients have underwent cholecystectomy because of symptomatic cholecystolithiasis (Group 2). Patients with mild acute pancreatitis were operated in the initial hospitalization. Groups were compared by age, race, previous abdominal surgery, severity of acute pancreatitis, leukocytosis, operative time, conversion to open surgery, postoperative complications, drain management, mortality rates and hospitalization period. Results: There were no differences regarding conversion rates to open surgery (p=0,34) and wound infection rates (p=0,32). There were no differences regarding postoperative hospitalization period in both groups (p=0,2406) (median 3 days in group 1 and 2 days in group 2). Fourteen patients had severe acute pancreatitis (16%) and open surgery was performed in 7 (50%) of these patients. In mild acute pancreatitis patients only 4 (4,1%) conversion to open surgery had occured. Cholecystectomy was performed, in 68 (94,4%) mild acute pancreatitis patients and in 12 (85,7%) severe form in the initial hospitalization. Conclusion: Laparoscopic cholecystectomy can be performed confidently during the index hospitalization after amelioration of the pancreatitis. However, the most important factor that affects the feasibility of laparoscopic cholecystectomy is the severity of the disease. Therefore, laparoscopic cholecystectomy should be postponed until the resolution of the pancreatic and peripancreatic inflammation.
Akut biliyer pankreatitte laparoskopik kolesistektomi
Keywords: Acute biliary pancreatitis; laparoscopic cholecystectomy; pancreatitis